Ownership Structure, Bank Stability and the Financial Performance of Commercial Banks in South Sudan - Bak Barnaba Chol; Elizabeth Kalunda Nthambi; Joseph Kamau (Fakultas Ekonomi, Universitas Bangka Belitung, 2020)
Since independence in 2011, the Republic of South Sudan has witnessed growth in the financial systems and the overall economy. This has led to growth in the number of financial institutions in the country. There is however minimal research on their overall performance. Hence the current research sought to determine the effect of ownership structure, bank stability and the financial performance of commercial banks in South Sudan. The population for the study was all the 29 commercial banks in South Sudan. Secondary data was collected for the period 2012-2017 from audited annual financial reports of individual banks and the Central Bank of South Sudan reports while primary data was collected by the use of a semi-structured questionnaire. Collected data was edited, sorted and coded into SPSS 23 for subsequent data analysis using SPSS 23 statistical analysis tool. This research utilized both descriptive and inferential statistical methods in the analysis. Statistical tests to be utilized in the study included t-tests, f-test, regression models and ANOVA models. Findings of the research were presented using frequencies, percentages, means, standard deviation, correlation coefficients, charts, tables, and other statistical measures. Results of the study indicated there was a statistically significant moderating effect of ownership structure on the financial performance of commercial banks in South Sudan. This study recommends that the government should adopt better measures to safeguard public-owned commercial banks to improve their efficiency and performance.